Model for adhesion clutch explains biphasic relationship between actin flow and traction at the cell leading edge. (13th May 2015) - Craig, Erin M; Stricker, Jonathan; Gardel, Margaret; Mogilner, Alex
Abstract: Cell motility relies on the continuous reorganization of a dynamic actin–myosin–adhesion network at the leading edge of the cell, in order to generate protrusion at the leading edge and traction between the cell and its external environment. We analyze experimentally measured spatial distributions of actin flow, traction force, myosin density, and adhesion density in control and pharmacologically perturbed epithelial cells in order to develop a mechanical model of the actin–adhesion–myosin self-organization at the leading edge. A model in which the F-actin network is treated as a viscous gel, and adhesion clutch engagement is strengthened by myosin but weakened by actin flow, can explain the measured molecular distributions and correctly predict the spatial distributions of the actin flow and traction stress. We test the model by comparing its predictions with measurements of the actin flow and traction stress in cells with fast and slow actin polymerization rates. The model predicts how the location of the lamellipodium–lamellum boundary depends on the actin viscosity and adhesion strength. The model further predicts that the location of the lamellipodium–lamellum boundary is not very sensitive to the level of myosin contraction.